Sugar: A Bittersweet History - Ljubica Milosavljević (University of Belgrade, 2016)
Review of the book by Elizabeth Abbott, Sugar: A Bittersweet History [Slatko-gorka istorija šećera]. 2009. Beograd: Geopoetika, 388. str.